2016
DOI: 10.5380/abclima.v18i0.43657
|View full text |Cite
|
Sign up to set email alerts
|

Tendências Do Controle Climático Oceânico Sob a Variabilidade Temporal Da Precipitação No Nordeste Do Brasil (Control Trends Oceanic Climate Under Temporary Variability of Rainfall in Northeast Brazil)

Abstract: RESUMO:Com significante diferença na distribuição espaço-temporal da chuva, prolongados períodos de deficiência hídrica, solos problemáticos e ausência de rios perenes, o sertão nordestino é a região mais vulnerável às mudanças climáticas no Brasil. Baseado em análise de dados climatológicos, este trabalho objetiva identificar tendências nas temperaturas da superfície do mar nos oceanos Atlântico Norte, Atlântico Sul, Pacífico Leste e Pacífico Central e a relação com a variabilidade temporal da precipitação em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Assessing the behavior of rainfall, Nóbrega et al (2016) found a trend of reduction in rainfall in Pernambuco State. The authors also emphasize that the irregular spatial-temporal distribution of rainfall in the Northeastern Sertão is associated to prolonged periods of water restriction and negatively influences the water level of rivers, turning this region more vulnerable to extreme events.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the behavior of rainfall, Nóbrega et al (2016) found a trend of reduction in rainfall in Pernambuco State. The authors also emphasize that the irregular spatial-temporal distribution of rainfall in the Northeastern Sertão is associated to prolonged periods of water restriction and negatively influences the water level of rivers, turning this region more vulnerable to extreme events.…”
Section: Resultsmentioning
confidence: 99%
“…When this occurs, it is referred to as extreme events, and the period of their occurrence can be classified as extreme years (Jorge and Lucena, 2018). Associated with these extreme events, climatic mechanisms are processes of ocean-atmosphere interaction that enable the formation of climate phenomena (Nóbrega et al, 2016;Pezzi et al, 2016). Accoring to Kelman (2019), among the climatic mechanisms contributing to the occurrence of extreme precipitation years, the El Niño-Southern Oscillation (ENSO) stands out.…”
Section: Influence Of Climatic Phenomena and Deforestation On Hydroen...mentioning
confidence: 99%
“…A série temporal de temperatura apresentou leve tendência de aumento, sendo a tendência anual igual a 0,0020 e 0,0833 em toda a série, sugerindo que a temperatura tende a aumentar, e o aumento na temperatura foi de 0,083°C. Este resultado condiz com estudos realizados por alguns autores (Marengo & Valverde, 2007;Tomasella et al, 2009;Nóbrega et al, 2011;Marengo, 2016;Dourado, 2017)…”
Section: Tendência Climática Por Mann-kendallunclassified